Physico-Geographic Changes Produced by Air Masses Convergence Within the Central Part of Romanian Plain. - Radu-Vlad DOBRI; Liviu APOSTOL; Lucian SFÎCĂ (Aerul şi Apa: Componente ale Mediului, 2019)
The central part of the Romanian Plain, more precisely the region delimited by the rivers Prahova and Mostistea to the East and Olt to the West, is characterized from a climatic point of view by more significant precipitation amount than the areas of the West and East, being named by Bordei-Ion (1988) as an air masses convergence area of directions from NE and E with directions from W. This area, due to the higher amount of precipitation, is evidenced by the characteristics of the physico-geographic factors such as, the types of vegetation, the characteristics of the soil cover, the use of the land or the presence of the steppes and the forests. The present work was realized using ROCADA data base (Bîrsan et al., 2014), from which all days with atmospheric precipitation values greater than 10 mm between 1981-2013 were extracted. This data was analyzed from a synoptic point of view using the available synoptic maps in the archive of the GFS forecasting model (Global Forecast System) available on www.wetter3.de. Thus, of the 3552 days analyzed, most days were asociated with high atmospheric instability specific for cold air advections in the form of long-wave troughs with a total of 1433 (40.3%). This is followed by Mediterranean cyclones with a total number of 1008 days (28.2%) with different trajectories according to the classification of Bordei-Ion (1983), of which cyclones with a type I track in 148 days (4.1%), cyclones with a type II track that acted in 653 days (18.4%) and those with trajectory IV that acted in 208 days (5.7%). The third place in the hierarchy of pluviogenetic causes is represented by the cyclones of Atlantic origin, with a total number of 436 days (12.3%). Cyclones with retrogressive trajectory had a 50 day (1.4%) and cut-off-low altitude cyclones in 469 days (13.4%). And last, warm air advections in anticyclonal regime acted in a number of 156 days (4,4%).